Bullet‐Shaped Magnetite Biomineralization Within a Magnetotactic Deltaproteobacterium: Implications for Magnetofossil Identification. Issue 7 (24th July 2020) - Li, Jinhua; Menguy, Nicolas; Roberts, Andrew P.; Gu, Lin; Leroy, Eric; Bourgon, Julie; Yang, Xin'an; Zhao, Xiang; Liu, Peiyu; Changela, Hitesh G.; Pan, Yongxin
Abstract: Magnetite produced by magnetotactic bacteria (MTB) provides stable paleomagnetic signals because it occurs as natural single‐domain magnetic nanocrystals. MTB can also provide useful paleoenvironmental information because their crystal morphologies are associated with particular bacterial groups and the environments in which they live. However, identification of the fossil remains of MTB (i.e., magnetofossils) from ancient sediments or rocks is challenging because of their generally small sizes and because the growth, morphology, and chain assembly of magnetite within MTB are not well understood. Nanoscale characterization is, therefore, needed to understand magnetite biomineralization and to develop magnetofossils as biogeochemical proxies for paleoenvironmental reconstructions. Using advanced transmission electron microscopy, we investigated magnetite growth and chain arrangements within magnetotactic Deltaproteobacteria strain WYHR‐1, which reveals how the magnetite grows to form elongated, bullet‐shaped nanocrystals. Three crystal growth stages are recognized: (i) initial isotropic growth to produce nearly round 20 nm particles, (ii) subsequent anisotropic growth along the [001] crystallographic direction to 75 nm lengths and 30–40 nm widths, and (iii) unidirectional growth along the [001] direction to 180 nm lengths, with some growing to 280 nm. Crystal growth and habit differ from that of magnetite produced by other known MTB strains, which indicates species‐specific biomineralization. These findings suggest that magnetite biomineralization might be much more diverse among MTB than previously thought. When characterized adequately at species level, magnetofossil crystallography, and apomorphic features are, therefore, likely to become useful proxies for ancient MTB taxonomic groups or species and for interpreting the environments in which they lived. Plain Language Summary: Biomineralization is a widespread process that provides living organisms with mineralized skeletons and organelles. Biominerals are mainly responsible for Earth's fossil record. As a striking example of microbial biomineralization, magnetotactic bacteria form intracellular chains of magnetic nanocrystals that they use to sense Earth's magnetic field. Their fossilized remains (magnetofossils) are being used increasingly to reconstruct paleomagnetic and paleoenvironmental information. However, magnetofossil identification remains challenging because magnetite particle growth and chain assembly processes are poorly understood. We report a species‐specific crystal growth and chain arrangement process in a novel magnetotactic strain WYHR‐1. Our findings suggest that magnetofossil crystallography could become a proxy for ancient bacterial taxonomic groups or species and for interpreting the environments in which they lived. Key Points: Magnetite produced by MTB carries stable paleomagnetic signals, but paleoenvironmental interpretation of biogenic magnetite is less obvious We find that magnetite crystals grow by a multistep process in a novel MTB to form highly elongated, bullet‐shaped magnetite Species‐specific magnetite biomineralization indicates that magnetite morphology is a proxy for ancient MTB taxonomic groups or species